Stem cells and regenerative medicine - Polak, Julia; Bishop, Anne (Henry Stewart Talks, 2007)
Regenerative medicine aims to repair, regenerate or replace damaged tissues and organs, Selection of appropriate cell sources, Plasticity, Differentiation of stem cells towards target phenotypes, Medium supplementation, Exposure to cell extracts, Direct or indirect co-culture with other cells/tissues, Genetic modification, Scaffolds, Bioprocessing systems, Pre-clinical testing of novel stem cell-based therapies in animal models of disease, Clinical trials, Treatment of ischaemic heart failure with autologous bone marrow stem cells